The FGG c.952G>A variant causes congenital dysfibrinogenemia characterized by recurrent cerebral infarction: a case report - Ying, Anna; Zhou, Yuanlin; Wang, Chunyue; Wang, Tao; Zhang, Xuan; Wang, Shanshan; Ke, Shaofa; Bao, Yuyan; Liu, Yang; Wang, Feng (Frontiers in Neurology, 2024)
Background: Congenital dysfibrinogenemia (CD) is a rare hereditary coagulation disorder resulting from mutations in fibrinogen genes. CD primarily presents with bleeding symptoms, but it can also lead to thrombotic events, including ischemic stroke. Case presentation: This report describes the case of a 52-year-old Chinese man who was admitted to the hospital twice due to recurrent cerebral infarction, characterized by sudden speech impairment and weakness in the right upper extremity. Brain MRI revealed multiple ischemic changes, predominantly in the left frontal and parietal lobes. Coagulation tests demonstrated reduced plasma fibrinogen (Clauss method), prolonged prothrombin time and thrombin time, and an elevated international normalized ratio. However, ELISA assay indicated elevated levels of fibrinogen γ-chain protein. Despite a two-month treatment regimen with aspirin, clopidogrel, and atorvastatin after the first hospitalization, the patient experienced a second ischemic stroke. Genetic analysis using Whole Exome Sequencing (WES) and Sanger sequencing identified a rare heterozygous missense variation FGG c.952G>A (rs267606810) in both the stroke patient and his asymptomatic sister. Both individuals exhibited the same alterations in fibrinogen, characterized by reduced functional levels but increased antigenic protein. Subsequently, the patient was diagnosed with ischemic stroke associated with congenital dysfibrinogenemia. Conclusions: This case report expands the clinical phenotype spectrum associated with FGG c.952G>A (rs267606810) and underscores the significance of considering CD as a potential etiology for unexplained ischemic stroke, particularly in patients with a family history of coagulation disorders.